Validation study of an acute bronchiolitis severity scale to determine admission to a paediatric intensive care unit - José Miguel Ramos-Fernández; Pedro Piñero-Domínguez; Pilar Abollo-López; David Moreno-Pérez; Ana María Cordón-Martínez; Guillermo Milano-Manso; Antonio Urda-Cardona (Elsevier, 2018)
Introduction: At present, there are few validated scoring tests for assessing acute bronchiolitis (AB) severity, and limited information on their test power. The aim of the present study is to evaluate the validity of an acute bronchiolitis severity score (ABSS) to help in deciding PICU admission. Patients and method: Prospective, descriptive, observational study of previously healthy infants under 1 year of age with AB, where the ABSS was used to compare severity as regards the need for PICU admission. The sample size was estimated as at least 175 patients. The research team was trained in the use of ABSS. All patients in the study were evaluated with ABSS daily, as well as in the case of clinical deterioration. The initial and maximum ABSS scores were contrasted to the need for PICU admission. A receiver operative curve was constructed, and the area under the curve was calculated, and the optimum point of sensitivity/specificity was estimated. Results: The study included a total of 190 patients (male/female: 58%/42%). PICU was required in 11 (6%). The mean ± SD ABSS-maximal score for patients who required and did not require PICU was 10.55 ± 1.12 and 6.35 ± 2.3, respectively (p < .001). The AUC for ABSS-maximal was 0.94 (p < .001, 95% CI: 0.90-0.98). The optimal cut-off point was set at ≥10 points for a sensitivity of 82% and a specificity of 91%. Conclusions: ABSS estimates the severity of AB regarding the need for PICU admission, with a sensitivity and specificity of clinical usefulness. Resumen: Introducción: En la actualidad existen pocas escalas validadas para valorar la bronquiolitis aguda (BA) y escasa información de su potencia de prueba. El objetivo del presente estudio es valorar la validez de una escala de severidad de BA (ESBA) para orientar los ingresos en UCIP. Pacientes y método: Estudio observacional prospectivo descriptivo de lactantes previamente sanos menores de un año con BA, donde se utilizó la ESBA para contrastar la gravedad con la necesidad de ingreso en UCIP. El tamaño de la muestra se estimó en al menos 175 pacientes. El equipo investigador fue entrenado en el uso de la ESBA. Todos los pacientes del estudio fueron evaluados con la ESBA diariamente y en caso de deterioro clínico. Se analizaron y compararon las puntuaciones ESBA inicial y máxima respecto a la necesidad de UCIP. Se construyó una curva operativa de receptor, se calculó el área bajo la curva y se estimó el punto óptimo de sensibilidad/especificidad. Resultados: Se incluyó a 190 pacientes (varón/mujer: 58%/42%). Precisaron UCIP 11 (6%). La puntuación media ± DE de la ESBA-máxima para pacientes que precisaron y no precisaron UCIP fue de 10,55 ±1,12 y 6,35 ±2,3, respectivamente. Esta diferencia fue significativa (p < 0,001). El ABC para la ESBA-máxima fue 0,94 (p < 0,001; IC del 95%: 0,90-0,98). El punto de corte óptimo se estableció en ≥ 10 puntos, para una sensibilidad del 82% y una especificidad del 91%. Conclusiones: La ESBA estima la gravedad de la BA respecto a la necesidad e ingreso en UCIP con una sensibilidad y especificidad de utilidad clínica.